Mission impossible: why crisis management missions do not increase the visibility of the European Union - Anderson, Stephanie B. (2013)
Abstract: The European Union’s (EU) Common Foreign and Security Policy (CFSP) and its accompanying Common Security and Defense Policy (CSDP) missions are tools used to increase the international profile of the EU. Using three different databases, this study features a content analysis that evaluates how much and what kind of media coverage CSDP missions receive. In general, the news coverage is positive, but limited. This article argues that the problem is structural: the very nature of the missions themselves, whether EU or NATO, makes them poor vehicles for EU promotion for political, institutional, and logistical reasons. By definition, they are conducted in the middle of crises, making news coverage politically sensitive. The very act of reporting could undermine the mission. Institutionally, all CSDP missions are intergovernmental; therefore, the member states control the coverage. Logistically, the missions are usually located in remote, undeveloped parts of the world, making it diffic